Differentiation and characterization of rat adipose tissue mesenchymal stem cells into endothelial‐like cells. (2nd November 2017) - Cannella, V.; Piccione, G.; Altomare, R.; Marino, A.; Di Marco, P.; Russotto, L.; Di Bella, S.; Purpari, G.; Gucciardi, F.; Cassata, G.; Damiano, G.; Palumbo, V. D.; et al.
Summary: In this study, mesenchymal stem cells were isolated from rat adipose tissue (AD‐MSCs) to characterize and differentiate them into endothelial‐like cells. AD‐MSCs were isolated by mechanical and enzymatic treatments, and their identity was verified by colony‐forming units (CFU) test and by differentiation into cells of mesodermal lineages. The endothelial differentiation was induced by plating another aliquot of cells in EGM‐2 medium, enriched with specific endothelial growth factors. Five subcultures were performed. The expression of stemness genes (OCT4, SOX2 and NANOG) was investigated. The presence of CD90 and the absence of the CD45 were evaluated by flow cytometry. The endothelial‐like cells were characterized by the evaluation of morphological changes and gene expression analysis for endothelial markers (CD31, CD144, CD146). Characterization of AD‐MSCs showed their ability to form clones, to differentiate in vitro and the OCT‐4, SOX‐2, NANOG genes expression. Immunophenotypic characterization showed the CD90 presence and the CD45 absence. The endothelial‐like cells showed morphological changes, the expression of CD31, CD144, CD146 genes and the presence of CD31 membrane receptor. Matrigel assay showed their ability to form network and vessels‐like structures. This study lays the foundations for future evaluation of the potential AD‐MSCs pro‐angiogenic and therapeutic role.